2016
DOI: 10.1083/jcb.201602038
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle–dependent phosphorylation of Sec4p controls membrane deposition during cytokinesis

Abstract: The GTPase Sec4p is a critical regulator of polarized membrane traffic. Lepore et al. show that the polo-like kinase Cdc5p phosphorylates Sec4p, which promotes coordinated membrane deposition during cytokinesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Correspondingly, the Ypt1 phosphomutant retained its localization to the Golgi yet was unable to provide the essential function of Ypt1. A previous study demonstrated that phosphorylation of another Rab GTPase, Sec4, is a negative regulatory mechanism coupled to the cell cycle 55 .…”
Section: D Phosphoproteome Analysis Provides Insights Into Function mentioning
confidence: 99%
“…Correspondingly, the Ypt1 phosphomutant retained its localization to the Golgi yet was unable to provide the essential function of Ypt1. A previous study demonstrated that phosphorylation of another Rab GTPase, Sec4, is a negative regulatory mechanism coupled to the cell cycle 55 .…”
Section: D Phosphoproteome Analysis Provides Insights Into Function mentioning
confidence: 99%
“…These results raise the possibility that abscission inhibition in cells with chromatin bridges requires modulation of exocyst-dependent, membrane-remodeling events at the abscission site. To gain insight into cytokinesis membrane trafficking events in cells with chromatin bridges, we followed the kinetics of the vesicle marker Sec4, which accumulates in the bud neck at the end of mitosis and controls membrane trafficking during cytokinesis ( Figure 8B ; Lepore et al. , 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the polo-like kinase triggers activation of both the FEAR and MEN pathways during anaphase, promoting Cdc14 release and activation [10]. Finally, Cdc5 kinase activity is also important to cytokinesis [161][162][163][164].…”
Section: Interplay Between the Mitotic Checkpoints: A Central Role Fomentioning
confidence: 99%